Learning Management System Acceptance Rate Among Vocational School Physics’ Student - Dwiastuti, Ety; Sukarelawan, Moh. Irma; Sriyanto, Sriyanto (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2022)
Learning management systems (LMS) have become a key component of teaching and learning in schools. However, the evaluation of student acceptance rates on its implementation so far has not been widely reported. Therefore, this study aims to evaluate the acceptance rate of LMS among students in terms of gender and grade level. The level of student acceptance of the LMS in administration through an online survey using Google forms. A total of 141 students who took physics subjects from class XI and XII, one of the vocational high schools were involved. Acceptance of the LMS uses a 21-item LMSAS (Learning Management System Acceptability Scale) developed by Sezer and Yilmaz in 2019. The LMSAS uses a 5-point Likert scale, from 1 (Strongly Disagree) to 5 (Strongly Agree). LMS acceptance components include Performance Expectancy (PE), Effort Expectancy (EE), Facilitating Condition (FC), and Social Influence (SI). Wright map and Logit Value of Person (LVP) were used to assess LMS acceptance among students. The analysis results show that student acceptance of the LMS is distributed chiefly at a good level of acceptance. As many as 84% of students received the LMS. Based on gender, 65% of male students are quite accepting of the LMS. Based on class, class XII students are more dominant (35.5%) receiving LMS. Thus, most students in public vocational high schools welcome the LMS well.